Sound Narrative: Honing a Deeper Understanding of Soundscapes - Walzer, Daniel (Revista Vórtex, 2020)
This essay reports on the pedagogical and curricular decisions guiding the creative activities in the author's university course incorporating field recording, soundscape-based composition, and digital technology. In keeping with the issue's theme of 21st-century composition, the article includes critical reflection and a consideration of the influence of R. Murray Schafer. It contextualizes the course in the broader context of modern compositional activities in university settings. The author's creative practice informs much of the pedagogical framework as a soundscape-based composer.